Assessment of Character and Religious Moderation Among Students: A Study on Learning Evaluation in Islamic Religious Education - Latif, Abdul; Windarsih, Ayu; Djakfar, Muhammad Zaki Ridho; Suwanto, Eko; Fauzan, Naufal Bani; Santosa, Sedya (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2026)
The growing phenomenon of intolerance and radicalization, which increasingly threatens the world of education in Indonesia, has created an urgent need to strengthen character assessment and religious moderation in Islamic Religious Education (PAI). This study aims to examine the concepts and techniques of character education assessment and religious moderation in PAI. The method used is qualitative research with a literature review approach through a search of sources from Scopus, Publish or Perish, and Google Scholar, with descriptive data analysis through data reduction, data presentation, and drawing conclusions. The review identified an integrated evaluation framework for Islamic Religious Education that combines cognitive, affective, and psychomotor assessment with the internalization of Islamic values and religious moderation. The framework synthesizes authentic assessment techniques, including structured observation, self- and peer-assessment, reflective journals, portfolios, project-based assessment, simulations, and standardized psychometric instruments, according to their respective strengths and limitations. Rather than relying on a single assessment method, the findings demonstrate that triangulating multiple assessment techniques provides a more valid, comprehensive, and continuous evaluation of students’ religious character and religious moderation, particularly in assessing tolerance, anti-violence attitudes, national commitment, and respect for cultural diversity. Abstrak: Fenomena intoleransi dan radikalisasi yang semakin mengancam dunia pendidikan di Indonesia mendorong kebutuhan mendesak akan penguatan penilaian karakter dan moderasi beragama dalam Pendidikan Agama Islam (PAI). Penelitian ini bertujuan mengkaji konsep dan teknik penilaian pendidikan karakter serta moderasi beragama dalam PAI. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan studi pustaka melalui penelusuran sumber dari Scopus, Publish or Perish, dan Google Scholar, dengan analisis data secara deskriptif melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil kajian menghasilkan suatu kerangka evaluasi terintegrasi dalam Pendidikan Agama Islam yang menggabungkan penilaian ranah kognitif, afektif, dan psikomotor dengan internalisasi nilai-nilai Islam dan moderasi beragama. Kerangka tersebut mensintesis berbagai teknik asesmen autentik, yaitu observasi terstruktur, penilaian diri dan teman sebaya, jurnal reflektif, portofolio, penilaian berbasis proyek, simulasi, serta instrumen psikometrik sesuai dengan kelebihan dan keterbatasan masing-masing. Temuan menunjukkan bahwa penggunaan satu teknik penilaian tidak mampu menggambarkan moderasi beragama secara utuh, sehingga diperlukan triangulasi berbagai teknik asesmen untuk menghasilkan evaluasi yang lebih valid, komprehensif, dan berkelanjutan terhadap karakter religius peserta didik, khususnya dalam mengukur toleransi, komitmen kebangsaan, penolakan terhadap kekerasan, dan penghargaan terhadap keberagaman budaya.